A visual fluoresce covalent organic polymer for precise analysis of Fe3+ in MC3T3-E1 cells: A method for bone disease diagnosis. (15th December 2021) - Li, Wenqiang; Xu, Changpeng; Huang, Lin; Huang, Zhiguan; Zhou, Bin; Li, Yuhe; Dong, Jianghui; Wang, Liping
Graphical abstract: Highlights: A new covalent organic polymer, PD-COP, was designed and synthesized. The toxicity experiments in cells indicted good biocompatibility of the PD-COP . PD-COP is a new material for the detection and monitoring of the concentration of Fe ions. Abstract: Precise detection of Fe 3+ ions in vitro is important for diagnosis of disease and bone health. Covalent organic polymers (COPs) are chosen as the precision probes, due to their light-weight, stable-bonds, and fast-response. In this work, a new fluorescent COP, pyrene-2, 7-diboronic-COP(PD-COP), was designed and its feasibility in detection of iron concentration in cells was tested. PD-COP showed good performance in selective detection of Fe 3+, among other metal ions. Its high anti-interference property and recyclability provide the theoretical basis for practical applications. PD-COP could selectively detect Fe 3+ ions with low limit of detection (LOD) at a concentration of about 0.68 µM. The quenching mechanism could be due to the transfer of electron. The in vitro experiments using cells also showed that the PD-COP had good biocompatibility, and the ability to detect Fe 3+ ions in cells. In conclusion, we successfully synthesized a novel COP, with high sensitivity that could selectively detect Fe 3+ ions. The COP had the ability to enter the cell membrane and combine with iron ions, which provided a new method of monitoring bone health.